SnO2/reduced graphene oxide nanocomposite as anode material for lithium-ion batteries with enhanced cyclability. - Jiang, W.; Zhao, X.; Ma, Z.; Lin, J.; Lu, Chunsheng (American Scientific Publishers, 2016)
SnO2 is considered as one of the most promising anode materials for next generation lithium-ion batteries, however, how to build energetic SnO2-based electrode architectures has still remained a big challenge. In this article, we developed a facile method to prepare SnO2/reduced graphene oxide (RGO) nanocomposite for an anode material of lithium-ion batteries. It is shown that, at the current density of 0.25 A·g−1, SnO2/RGO has a high initial capacity of 1705 mAh·g−1 and a capacity retention of 500 mAh·g−1 after 50 cycles. The total specific capacity of SnO2/RGO is higher than the sum of their pure counterparts, indicating a positive synergistic effect on the electrochemical performance.